Meningkatkan Kemampuan Komunikasi Matematis Siswa Dan Self Confidence Melalui Penerapan Model Problem Based Learning Di SMA Negeri 1 Tanjung Morawa - Grace Stela Lely Hasugian; Dwi Novita Sari; Ramadhani Ramadhani; Burlianda Burlianda; Masniawita Gloria Sinaga (Journal on Education, 2024)
The objective of this classroom action research is to determine the improvement in students' mathematics communication abilities and self-confidence resulting from the implementation of the Problem Based Learning learning model. The research subjects consisted of 26 students from Class XI-Creative at SMA Negeri 1 Tanjung Morawa. The analysis of data on students' mathematical communication abilities in cycle I revealed that only 11 students, representing 42.30% of the total, met the criteria by scoring at least 70. The results indicated that the level of classical completeness fell short of the minimum threshold of 85%. In the second cycle, it was observed that 23 students, equivalent to 88.46% of the total student population, successfully met the desired communication level by attaining a minimum score of 70. The number of pupils who have achieved learning mastery has grown by 12. In Cycle I, there was a 14.49 rise in mathematical communication abilities, with an average score of 64.95 on the communication skills test. In Cycle II, the skills climbed to 79.44. Regarding students' self-confidence in the pre-cycle, the study revealed that 49.45% of students had trust in their own talents. This percentage grew to 59.89% in cycle I and further improved to 77.74% in cycle II. Regarding students' self-confidence in the pre-cycle, the study revealed that 51.8% of students demonstrated independent decision-making. This percentage grew to 65.62% in the first cycle and further rose to 78.6% in the second cycle. Regarding students' self-confidence in the pre-cycle, the study revealed that students had a favourable self-perception of 49.4%. In cycle I, this percentage rose to 62.3%, and in cycle II, it further grew to 78.75%. Regarding students' self-confidence in the pre-cycle, it was observed that 50% of students had the bravery to voice their ideas. In the first cycle, this percentage increased to 67.4, and in the second cycle, it further rose to 75.59. The use of the problem-based learning paradigm in the subject of systems of linear equations in two variables at SMA N 1 Tanjung Morawa has resulted in an improvement in students' mathematical communication.